Development and Applications of Somatic Embryogenesis in Grapevine (Vitis spp.) - Angela Carra; Akila Wijerathna-Yapa; Ranjith Pathirana; Francesco Carimi (Plants)
Somatic embryogenesis (SE) provides alternative methodologies for the propagation of grapevine (Vitis spp.) cultivars, conservation of their germplasm resources, and crop improvement. In this review, the current state of knowledge regarding grapevine SE as applied to these technologies is presented, with a focus on the benefits, challenges, and limitations of this method. The paper provides a comprehensive overview of the different steps involved in the grapevine SE process, including callus induction, maintenance of embryogenic cultures, and the production of plantlets. Additionally, the review explores the development of high-health plant material through SE; the molecular and biochemical mechanisms underlying SE, including the regulation of gene expression, hormone signaling pathways, and metabolic pathways; as well as its use in crop improvement programs. The review concludes by highlighting the future directions for grapevine SE research, including the development of new and improved protocols, the integration of SE with other plant tissue culture techniques, and the application of SE for the production of elite grapevine cultivars, for the conservation of endangered grapevine species as well as for cultivars with unique traits that are valuable for breeding programs.